Aerobic and Anaerobic Bacterial Isolates on the Surface and Core of Tonsils from Patients with Chronic Tonsillitis - Meera Niranjan Khadilkar; Nitin Ankle; Sheetal Harakuni (Bengal Journal of Otolaryngology and Head Neck Surgery, 2017)
Introduction